Three-dimensional structure of the complex between calmodulin mutant lacking the c-terminal five residues and the calmodulin-binding peptide derived from skeletal muscle myosin light-chain kinase - Dung, Vu Van; Umetsu, Yoshitaka; Ohki, Shinya (Academia Journal of Biology, 2017)
In our previous study, functional ability and conformational stability had been examined for C-terminal deletion mutants of a 148-residue Ca2+-binding protein, chicken calmodulin (CaM). In that study, we had reported that a mutant named CCMΔ5, missing five residues at the C-terminus, activates CaM-target as much as full-length CaM does. This finding is intriguing because CCMΔ5 lacks the key residues, Met144 and Met145, for the target activation. To uncover why CCMΔ5 displays proper function, here we report the three-dimensional structure of CCMΔ5 bound to the peptide derived from skeletal muscle myosin light-chain kinase (skMLCK). The structure determination was achieved using multidimensional nuclear magnetic resonance (NMR) spectroscopy. The complex structure of CCM∆5-skMLCK was compared to that of wild CaM-skMLCK. The results showed that the orientation of helix-1 and helix-5 in CCM∆5 differs from those in wild CaM. Moreover, distinctive hydrophobic interaction manner was found in the binding between CCM∆5 and peptide; Phe141, Ala128, Met109, Leu105 and Phe92 of CCM∆5 contribute to the interaction with Trp4 of the skMLCK peptide. Abbreviations: CaM, calmodulin; CCMΔX, a deletion mutant of CaM that lacks X C-terminal residues; NMR, Nuclear magnetic resonance; PDB, Protein date bank; skMLCK, skeletal muscle myosin light-chain kinase; TOF-MS, Time-of-flight mass spectrometry; RMSD, root mean square deviation; SDS-PAGE, Sodium dodecyl sulfate polyacrylamide gel electrophoresis Citation: Vu Van Dung, Umetsu Y., Ohki S., 2017. Three-dimensional structure of the complex between calmodulin mutant lacking the c-terminal five residues and the calmodulin-binding peptide derived from skeletal muscle myosin light-chain kinase. Tap chi Sinh hoc, 39(3): 309-319. DOI: 10.15625/0866-7160/v39n3.10111. *Corresponding author: vandungbio46@yahoo.com Received 19 June 2017, accepted 20 August 2017